1990
DOI: 10.1530/acta.0.1230504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxytocin upon the endocrine pancreas secretion and glucose turnover in normal man

Abstract: Abstract. In normal man oxytocin infusion under basal conditions and at pharmacological doses evoked a rapid surge in plasma glucose and glucagon levels followed by a later increase in plasma insulin levels. Simultaneous [D-3H]glucose infusion indicated that oxytocin also produced a prompt and significant increase in hepatic glucose output with a secondary increase in glucose disappearance rate. Eight healthy volunteers were studied during euglycemic glucose clamp and simultaneous [D-3H]glucose infusion, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The role of AVP and OT during hypoglycemia is still unclear. Both hormones are presumed to contribute to glucose homeo stasis because of their hyperglycemic effects [18][19][20][21][22][23][24], However, these actions have been described at concentra tions higher than those reported during ITT in normal human subjects. On the other hand, elevated AVP and OT responses to hypoglycemia have been found in diabetics [25][26][27], Furthermore, posterior pituitary hormones are known to act as neuromodulators of other hormonal se cretions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AVP and OT during hypoglycemia is still unclear. Both hormones are presumed to contribute to glucose homeo stasis because of their hyperglycemic effects [18][19][20][21][22][23][24], However, these actions have been described at concentra tions higher than those reported during ITT in normal human subjects. On the other hand, elevated AVP and OT responses to hypoglycemia have been found in diabetics [25][26][27], Furthermore, posterior pituitary hormones are known to act as neuromodulators of other hormonal se cretions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in response to insulin-induced hypoglycaemia, oxytocin infused intravenously at this dose attenuated the drop in levels of glucose, increased levels of glucagon and adrenaline and reduced cortisol levels 111,112 . Using a euglyceamic euinsulinaemic clamp, it was also shown that the same dose of intravenous oxytocin increased hepatic glucose output in healthy young men aged 22-28 yrs 113 .…”
Section: Glucose Homeostasismentioning
confidence: 95%
“…Although other non-glucose secretagogues, such as isoproterenol, are also used in provocative tests of beta cell function [26], bolus administration of isoproterenol is less effective than arginine in stimulation of acute glucagon release in humans [27]. Acute insulin-induced hypoglycaemia has also been used to assess alpha cell [9] NEFA [8] Parasympathetic nerves [10] Ketones [7] Adrenaline (epinephrine) [112] Insulin [113] Oxytocin [114] Somatostatin [115] Vasopressin [116] Secretin [117] GIP [118] GLP-1 [54] PACAP [119] Carbohydrate meal [18] GRP [120] CCK [121] VIP [122] Protein meal [18] Stress [20] Hypoglycaemia [3] GRP gastrin-releasing peptide; PACAP pituitary adenylate cyclaseactivating polypeptide; VIP vasoactive intestinal polypeptide function in humans [28], although arginine stimulation tests clearly pose less risk and are more routinely employed.…”
Section: Clinical Measures Of Alpha Cell Functionmentioning
confidence: 99%